Effect of playing position and time on-court on activity profiles in german elite team handball - Büchel, D.; Jakobsmeyer, R.; Döring, M.; Adams, M.; Rückert, U.; Baumeister, J. (International Journal of Performance Analysis in Sport, 2019)
On-court activity profiles in team-handball can help coaches to individualise conditioning programmes for the purposes of performance enhancement and return to performance. The aim of our study was to quantify on-court activity in an independent sample of elite team-handball players related to playing positions and playing time. 16 matches of a german first division squad were recorded by two ceiling cameras. Based on trajectory data of semi-automatic tracking windows, we quantified activity of 168 players. Wings (n = 44) showed higher absolute activity due to increased time on-court (51.0 ± 20.9 min) and distance covered (4057.9 ± 1630.5 m) compared to backcourts (n = 93; 35.8 ± 16.5 min; 2881.96 ± 1239.29 m) and pivots (n = 31; 35.4 ± 15.8 min; 2702.8 ± 1180.0 m). Furthermore, times and distances at different intensities differed significantly between positions (p < .001). Wings covered more distance standing (1.09% ± 0.2%) and sprinting (9.8% ± 2.2%) compared to backcourts (0.7% ± 0.3%; 33.4 ± 2.0%) and pivots (0.9% ± 0.2%; 4.4% ± 1.8%). Low time players (1.4 ± 0.2 m/s) moved significantly quicker compared to high time players (1.3 ± 0.1 m/s, p = .003). Activity profiles in handball are modulated by playing position and playing time. The present data may help individualising training programmes according to on-court demands to enhance performance.